Pomnik żołnierzy poległych w I wojnie światowej w Przytoku = World War I memorial monument in Przytok - Ostrowski, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article describes a brief historical outline of a small village Przytok, where a piece of a monument dedicated to citizens of a village fallen in the Great War survived on a communal cemetery. It begins with the description of commemoration of soldiers who died in military actions and then the evolution of this process is presented. As a result it led to establishing new war graveyards and founding monuments dedicated to fallen soldiers.
Keywords: Przytok (pow. zielonogórski) - historia; I (pierwsza) wojna światowa; pomnik poległych; losy żołnierzy; Word War I; War memorials; fate of soldiers